Morinda citrifolia L. (Noni) fruits: Optimising extraction kinetics of yield and flavonoids for enhanced antioxidant activity at different temperatures - Tun Faiz Al Hakim Tun Faisal Ismail; Mohammad Amil Zulhilmi Benjamin; Mohd Azrie Awang (Faculty of Engineering, Khon Kaen University, Muang, Khon Kaen, 2024)
Morinda citrifolia L., commonly known as ‘Noni’, holds significant potential in pharmaceutical research due to its bioactive constituents. This study aimed to optimise the ultrasound-assisted extraction process for yield and total flavonoid content (TFC) from M. citrifolia fruits at different temperatures (40 °C, 50 °C, and 60 °C). The extraction kinetics were analysed using four models: first-order kinetic, Peleg, power law, and two-site kinetic, determined through goodness-of-fit. Antioxidant activity was measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. Results showed the peak extraction yield at 40 °C within 90 min, yielding 1.46 ± 0.01 mg/mL, while the peak TFC was at 50 °C within 100 min, yielding 3.43 ± 0.00 mg CE/g db. The two-site kinetic model best described the extraction kinetics based on goodness of fit. The IC50 value for DPPH inhibition was 1883.57 ± 0.02 µg/mL at 50 °C, indicating moderate antioxidant activity compared to ascorbic acid (95.11 ± 0.13 µg/mL). Overall, M. citrifolia fruits provide valuable insights for standardised extraction methods, potentially benefiting therapeutic applications and indirectly reducing operational costs and time for manufacturers.